Identification and virtual screening of novel salty peptides from hydrolysate of tilapia by-product by batch molecular docking - Ren, Hongjun; Zhou, Jingxuan; Fu, Huixian; Feng, Qiaohui; Wang, Jionghao; Li, Chuan; Xia, Guanghua; Shang, Wenting; He, Yanfu (Frontiers in Nutrition, 2024)
Introduction Tilapia produces a large number of by-products during processing, which contain potentially flavorful peptides. Methods The application of PyRx software enabled batch molecular docking andscreening of 16 potential salty peptides from 189 peptides identified in the enzymaticdigestion of tilapia by-products. Results According to sensory analysis, all 16 peptides werepredominantly salty with a threshold of 0.256 - 0.379 mmol/L with some sournessand astringency, among which HLDDALR had the highest salty intensity, followedby VIEPLDIGDDKVR, FPGIPDHL, and DFKSPDDPSRH. I addition, moleculardocking results showed these four core peptides with high salt intensity bound to thesalt receptor TRPV1 mainly via van der Waals interactions, hydrogen bonds, andhydrophobic forces; Arg491, Tyr487, VAL441, and Asp708 were the key sites for thebinding of salty peptides to TRPV1. Therefore, the application of batch moleculardocking using PyRx is effective and economical for the virtual screening of saltypeptides.